(untitled) (Journal of Hama University, 2019)
Recently, the studies and researches carried out to protect the steel structures against corrosion have increased from corossion to ensure the continuity of the high durability of these installations over the long run and to reduce the economic cost resulting from the maintenance and continuous repairs of the steel structures. The results of most of these researches and studies indicate that Hot-Dip Galvanizing These steel sections are the optimum solution that reduces the cost of maintenance and repairs in the steel structures and thus the continuity of the high durability of the steel structures. The objective of this research is to provide an overview of the economic advantages of hot zinc galvanization for cold-formed steel sections by comparing three types of cold sheeting: non-shielded sheets with protective materials and hand-painted sheets with paint and hot zinc immersed sheets by conducting experiments Laboratory testing of plate tensile, therefore,knowledge of the mechanical properties of the three samples, The results showed that zinc-hot galvanized samples were almost unaffected by water immersion, while samples coated with paint and non-shielded samples decreased the values of yield stress and Refraction stress by different rates.